IMPLEMENTASI SUPPLY CHAIN MANAGEMENT UNTUK PENGADAAN OBAT PADA APOTEK MANFAAT - Maya Yunia Irianti (FKOM UNIKU, 2017)
Nowdays, information technology has become an important part of human life. By using information technology, people can do the task more quickly. It will certainly give many advantages in increasing productivity of the organization, job efficiency, and cost savings. Manfaat Pharmacy in drug procurement activities still uses manual technique such as supplier come to pharmacies to offer the drugs, a buildup of drugs that can cause drug expiration due to difficulties in controlling the drug’s stock, and also it has difficulty in making reports related to the process of drug procurement. Therefore, it needs a system that can help the process of drug procurement quickly and precisely. The method applied in this research is Supply Chain Management (SCM), which is an approach to make efficient integration between suppliers, manufacturers, distributors, retailers, and consumers. This research produces a drug procurement system that helps the process of drug procurement quickly and precisely. This drug procurement system is built with system design DFD, ERD, and based on PHP and MySQL.Keywords: Information Technology, Drug Procurements, SCM, PHP, MySQL